Service Operations Dynamics Managing in an Age of Digitization, Disruption and Discontent - Akkermans, Henk (Springer International Publishing, 2018)
This innovative book presents an up-to-date account of service operations, spanning topics such as IT-enabled services, service supply chain and volatility of demand and supply. Combining a systems perspective with a focus on service supply chains, the chapters provide a clearly framed set of mechanisms and theories with a focus on innovation-driven sectors and the game-changing role of IT. With each chapter built around real-life examples and service companies, the primary services supply chain is discussed alongside four key stakeholder groups: workforce, customers and markets, buyers and suppliers, and IT and innovations.